2012
DOI: 10.1016/j.schres.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory deficits in a virtual reality eight-arm radial maze in schizophrenia

Abstract: Learning and memory impairments are present in schizophrenia (SZ) throughout the illness course and predict psychosocial function. Abnormalities in prefrontal and hippocampal function are thought to contribute to SZ deficits. The radial arm maze (RAM) is a test of spatial learning and memory in rodents that relies on intact prefrontal and hippocampal function. The goal of the present study was to investigate spatial learning in SZ using a virtual RAM. Thirty-three subjects with SZ and thirty-nine healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 48 publications
5
53
0
2
Order By: Relevance
“…Impaired information processing during WM has been found to be a core cognitive deficit in schizophrenia (Barch and Ceaser, 2012) and has also been observed during normal aging (Nagel et al, 2009). Virtual navigation paradigms have already been successfully used in aged subjects and in clinical populations (Konishi et al, 2013;Sneider et al, 2013;Spieker et al, 2012;Yuan et al, 2014). Although there are currently no established treatments for such deficits, the use of this translational paradigm in affected populations is expected to help identify the neural correlates of WM impairment and may ultimately inform novel treatments (Millan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired information processing during WM has been found to be a core cognitive deficit in schizophrenia (Barch and Ceaser, 2012) and has also been observed during normal aging (Nagel et al, 2009). Virtual navigation paradigms have already been successfully used in aged subjects and in clinical populations (Konishi et al, 2013;Sneider et al, 2013;Spieker et al, 2012;Yuan et al, 2014). Although there are currently no established treatments for such deficits, the use of this translational paradigm in affected populations is expected to help identify the neural correlates of WM impairment and may ultimately inform novel treatments (Millan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a virtual maze task, patients with schizophrenia performed worse than healthy controls on speed, attention, and working and spatial memory. [13][14][15] An fMRI study showed that various brain regions were activated during a virtual maze task in schizophrenia patients and controls, but that task-related neural circuits identified in patients did not correspond well with regional neuroanatomy. 16 Cognitive problems in goal-directed navigation were also found in naturalistic virtual environments such as finding targets in a city.…”
Section: Cognition and Social Behaviormentioning
confidence: 99%
“…Por otra parte, aunque la memoria espacial ha sido ampliamente investigada en humanos expuestos a entornos virtuales y reales (Chamizo, Aznar-Casanova & Artigas, 2003;Goodrich-Hunsaker et al, 2009;Hardt, Hupbach & Nadel, 2009;Jacobs, Laurance & Thomas, 1997;Schoenfeld, Foreman & Leplow, 2014;Spieker, Astur, West, Griego & Rowland, 2012;Ross, Skelton & Mueller, 2006), los estudios que abordan el efecto del paso del tiempo en la retención de la memoria espacial son actualmente escasos, y la mayoría de ellos han sido conducidos como diseños de caso único que analizan la memoria espacial de pacientes con daño en la cara medial del lóbulo temporal, incluyendo el HC.…”
Section: Introductionunclassified
“…Así, validar una metodología para el estudio de la memoria espacial a largo plazo en humanos sería de utilidad para describir y comparar sus característi-cas en poblaciones sanas y en poblaciones clínicas, lo que sería también una potencial herramienta de diagnóstico e incluso para la evaluación de tratamientos farmacológicos (Schoenfeld et al 2014;Spieker et al, 2012).…”
Section: Introductionunclassified